Failure Modes in Concrete Repair Systems due to Ongoing Corrosion. (2nd April 2017) - Luković, Mladena; Šavija, Branko; Ye, Guang; Schlangen, Erik; van Breugel, Klaas
Abstract : Corrosion of steel reinforcement is the main cause of deterioration in reinforced concrete structures. It can result in cracking and spalling of the concrete cover. After the damaged cover is repaired, reinforcement corrosion might continue and even accelerate. While the development of the corrosion cell is difficult to control, the damage can be possibly delayed and controlled by use of a suitable repair material. The lattice fracture model is used in this paper to investigate the performance of strain hardening cementitious composite (SHCC) in concrete repair systems exposed to ongoing corrosion. Numerical results were verified by experimental tests when SHCC, nonreinforced material (repair mortar), and commercial repair mortar are used as repair materials. In experiments, reinforcement bars (surrounded by a repair material) were exposed to accelerated corrosion tests. The influence of the substrate surface preparation, the type of repair material, the interface, and the substrate strength on the resulting damage and failure mode of repair systems are discussed. In general, SHCC repair enables distributed cracking with small crack widths, up to several times smaller compared to repair mortar. Furthermore, more warning signs prior to the final failure are present in the SHCC repair system.